Recycled materials to stabilise rammed earth: Insights and framework - Carraro,JAH (2015)
From a fundamental soil mechanics standpoint, rammed earth is an unsaturated compacted soil mixture that can have inter-particle bonding and reinforcing elements. The mechanical behavior of rammed earth can thus be interpreted using a rigorous geomechanics framework. In this paper, fundamental concepts required to analyse stabilised soil mixtures are outlined, with a particular focus on soil fabric, cementation and fiber-reinforcement issues. Assessment of specific gravity, particle shape, particle size distribution, plasticity, and volumetric indices of all fractions in a soil mixture can be useful for the rational (non-empirical) design of such materials, including rammed earth. Recent research on the beneficial use of waste materials in soil stabilisation is summarised with a focus on techniques aiming at increasing stiffness and strength, mitigating swell potential and improving thermal conductivity of stabilized soil mixtures. The successful use of waste materials such as carbide lime, scrap tire rubber, waste fibers, and various types of fly ash in soil stabilisation applications is highlighted. The potential use of alternative waste materials within a rational and mechanistic design framework that may be useful for rammed earth is discussed.